EFFECTS OF SOIL VISCOSITY, SOIL TEMPERATURE, AND SPECIFIC GRAVITY ON PLANTS GROWTH SOWN IN SOIL PREPARED FROM LABORATORY CHEMICAL WASTE - Rai, Preeti; Chatrath, Harsha (International Journal of Students’ Research in Technology & Management, 2019)
Purpose of the study: The primary purpose of this study is to find out the effect of change in soil viscosity, soil temperature, and specific gravity on growth of plants sown in the soil prepared from laboratory chemical waste collected from an educational institute and with the plants sown in average soil. Methodology: Three-three pots with different soil combinations mixed with solid and liquid chemical waste have been used for growing A. barbadensis Mill, Saussurea obvallata, and Lilium plants. Observations were made every fifteen days for three months by checking plant height, the number of leaves, the color of leaves, and soil temperature for understanding and comparing plant growth with respect to variation in temperature. Later on, density and viscosity of soils have also been checked with specific gravity bottle and viscometer help. Main Findings: Plants’ growth differs with variation in soil viscosity, soil temperature, and soil density. All plants cannot grow potentially at the same temperature, viscosity, and density. A. barbadensis Mill A4 has shown better growth with the least viscosity and highest particle density of soil. Saussurea obvallata BK1 has shown better growth with the least viscosity and least particle density of soil. Lilium L1 has shown better growth with all the moderate values of soil. Applications of this study: This study helped to understand that all the plants have their requirements of nutrients, nutrition, and physical factors for their growth. The study also helped to understand that although the soil has taken initially is the same, viscosity and density of the soil changes due to the plants grown in it. Novelty/Originality of this study: The use of chemical wastes is taken into consideration instead of fertilizers to reduce pollution.